The effect of liquid organic hydrogen carrier on the physico-mechanical and rheological properties of injection-molded high-density polyethylene and polyketone - Jyothsna Surisetty; Zahra Shahroodi; Thomas Lucyshyn; Gernot Oreski (Results in Engineering)
Semi-crystalline polymers play an important role in the storage of fuels in automotive tanks due to their barrier properties and chemical resistance. A liquid organic hydrogen carrier (LOHC) consisting of hydrogen from renewable sources has been chosen as an alternative to fossil fuels and is considered green energy. This study investigates the effect of LOHC on mechanical and rheological properties of high-density polyethylene (HDPE) and polyketone (POK). HDPE has been extensively studied and is used in numerous fuel tank applications. POK, on the other hand, is being considered due to its low carbon footprint compared to polyamides and polyoxymethylene. The immersion of HDPE in LOHC for 500 h at 25 and 60 °C resulted in a decrease in flexural properties. In addition, energy absorption increased after aging at 25 °C and decreased at 60 °C showing ductile behavior. Dynamic mechanical analysis (DMA) results showed an overall decrease in storage modules in all the aged samples of HDPE. The same phenomenon was observed in rheology measurements after immersion in LOHC: the complex viscosity decreased in all samples. POK, on the other hand, showed an opposite trend, with increasing immersion time the flexural modulus also increased due to changes in crystallinity. In the drop-weight impact test, POK showed both ductile and brittle characteristics, independent of immersion time and temperature. The DMA results in POK revealed minimal changes in stiffness during temperature shifts which was recorded up to 90 °C, but the storage modulus was almost in the same range for unaged and aged samples.